2018
DOI: 10.1519/jsc.0000000000002100
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Conditioning Capacities and Shooting Performance in Professional Basketball Players: An Analysis of Stationary and Dynamic Shooting Skills

Abstract: Pojskic, H, Sisic, N, Separovic, V, and Sekulic, D. Association between conditioning capacities and shooting performance in professional basketball players: an analysis of stationary and dynamic shooting skills. J Strength Cond Res 32(7): 1981-1992, 2018-Little is known about the influence of conditioning capacities on shooting performance in basketball. The aim of this study was to examine the relationship between different conditioning capacities and shooting performance in professional basketball players. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 18 publications
6
39
0
1
Order By: Relevance
“…The shot order of the BJSAT ensured athletes were alternating between two-and threepoint shooting distance and not performing consecutive jump shots from either distance throughout the test. This feature of the BJSAT more closely replicates in-game shooting patterns (Gomez, et al, 2017) compared to jump shooting assessments previously undertaken in basketball that involve successive shot attempts from the same shooting distance (Erculj & Supej, 2009;Pojskic, et al, 2011;Pojskic, Sisic, Separovic, & Sekulic, 2017).…”
Section: Basketball Jump Shooting Accuracy Test Developmentsupporting
confidence: 52%
“…The shot order of the BJSAT ensured athletes were alternating between two-and threepoint shooting distance and not performing consecutive jump shots from either distance throughout the test. This feature of the BJSAT more closely replicates in-game shooting patterns (Gomez, et al, 2017) compared to jump shooting assessments previously undertaken in basketball that involve successive shot attempts from the same shooting distance (Erculj & Supej, 2009;Pojskic, et al, 2011;Pojskic, Sisic, Separovic, & Sekulic, 2017).…”
Section: Basketball Jump Shooting Accuracy Test Developmentsupporting
confidence: 52%
“…These results could be associated with a possible better physical performance for winning compared to losing teams. In fact, previous investigations revealed a positive correlation between vertical jump performance and three-point shooting accuracy over a season [ 20 , 21 ]. Specifically, Pojskic et al [ 21 ] suggested that players with higher vertical jump capacities are able to perform the shot with a lower release velocity, allowing more time for proper shooting execution.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous investigations revealed a positive correlation between vertical jump performance and three-point shooting accuracy over a season [ 20 , 21 ]. Specifically, Pojskic et al [ 21 ] suggested that players with higher vertical jump capacities are able to perform the shot with a lower release velocity, allowing more time for proper shooting execution. Therefore, further studies should investigate the difference of anaerobic performance in association with shooting accuracy between winning and losing college teams during games.…”
Section: Discussionmentioning
confidence: 99%
“…Modern concepts in the theory and method of sports training on the development of jumping are reduced to the fact that the use of exercises mainly of a jump character contributes to improving only the speed of repulsion, and the use of exercises power and speed-force character provides growth and speed, and the forces of repulsion. It should be considered proven position on the necessity of the predominant development of speed-strength properties of the muscles, in combination with exercises to increase mobility in the joints and relaxation in order to develop jerking and inter-muscular coordination (Padulo, Nikolaidis, Cular, Dello Iacono, Vando, Galasso, Ardigo, 2018, Podmenik, Supej, Coh, & Erculj, 2017Pojskic, Sisic, Separovic, & Sekulic, 2018). An open question remains about the qualitative parameters of the training effects of power and speed-force orientation, which ensure the development and support of the achieved level of jumping.…”
Section: Jpes ®mentioning
confidence: 99%